Knowledge of the patients of the Department of Obstetrics and Gynaecology about lactation and breastfeeding during the Covid-19 pandemic and before the pandemic - a comparative study - Karolina Detka; Anna Zwierzyńska; Jakub Gruszka; Grzegorz Świercz; Olga Adamczyk-Gruszka (Kazimierz Wielki University, 2021)
Introduction The mammary gland is a paired skin gland of women, responsible for the lactation process. It is synchronized with the operation of the endocrine system. The production of breast milk takes place after childbirth through the action of the hormonal and nervous systems. Secretion is controlled by prolactin and oxytocin. Its composition includes: proteins, fats, carbohydrates, minerals and vitamins. It is rich in stem cells. The function of the gland is to secure the nutritional and energy needs of the newborn. Aim of the work The aim of the study was to evaluate and compare the knowledge of the patients of the Department of Obstetrics and Gynaecology, WSZZ in Kielce about lactation and breastfeeding before and during the Covid-19 pandemic -a comparative study. Material and methods 420 puerperae participated in the study. The first pre-COVID-19 pandemic group included 196 women, the second group during the pandemic period included 224 respondents. Among the puerperae, women aged over 30 constituted the most numerous age group. The Bioethics Committee of UJK (Jan Kochanowski University of Kielce) approved the study No. 16/2021. Statistical analysis was performed with the use of the Statistica computer program. Results The patients living in the city have more knowledge about lactation and breastfeeding than the patients from rural areas. The older the patient and the greater the number of completed pregnancies and deliveries, the greater the knowledge about lactation and breastfeeding. The assessment of the involvement of medical personnel depends on the time when the patient gave birth. The period of the COVID-19 pandemic has impacted the knowledge about reducing the risk of breast cancer in women. The patients from the pandemic period are more knowledgeable about breastfeeding and lactation than patients in the pre-pandemic period.